(untitled) (Tanzania Medical Journal, 2025)
Background Information about renal insufficiency and associated risk factors among people living with HIV (PLHIV) infection in East Africa is limited. The aim of this study was to determine the prevalence and factors associated with moderate to severe renal insufficiency among PLHIV in Dar es Salaam, Tanzania. Methods A cross-sectional analysis of the baseline clinical data for 30,822 PLHIV who enrolled at the Management and Development for Health - Care and Treatment Clinics (MDH-CTCs) in Dar es Salam, Tanzania was done. Moderate to severe renal insufficiency was defined as estimated glomerular filtration rate (eGFR) < 60mL/min/1.73m2 based on the CKD-EPI equation. Poisson regression models weighted by the inverse probability of inclusion in the study were used to estimate prevalence ratios for predictors of renal insufficiency. Results Our study population was relatively young [median age (IQR) of 35 (17-50) years], predominantly female (57% non-pregnant, 13.1% pregnant of all participants), and the majority (90.6%) were ART (Anti-Retroviral Therapy) naïve. The overall prevalence of moderate to severe renal insufficiency was 8.2%. In multivariable adjusted analysis, moderate to severe renal insufficiency was significantly associated with older age (i.e. ≥ 50 years) [Prevalence Ratio (PR) 2.16, 95% CI (1.70-2.75)], mid-upper-arm circumference under 22 cm [PR 1.48 (1.06, 2.07)], CD4+ cell counts of < 50 cells/mm3 [PR 1.43(1.10-1.85)]; and WHO HIV/AIDS stage IV [PR 16 2.09(1.40-3.11)]. Conclusion Moderate to severe renal insufficiency is prevalent among PLHIV enrolled at Care and Treatment Centers in Dar es Salaam, Tanzania. In particular, older patients with advanced HIV/AIDS stage and poor liver function are more likely to present with moderate to severe renal insufficiency. However, further studies to explore the causal relationship between these associated risk factors and the outcomes (renal insufficiency) are warranted.